The Effect Of The Mobile Reporter Strategy in Improving Some Basic Football Skills For Students - Haider Ahmed Shihab (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Modern teaching strategies are among the most important programs that aim to improve the performance of students in the field of physical education, which contributes to enhancing the roles of learners from negative to positive in general or in particular, so many teachers seek to motivate their students towards learning and mastering sports skills and improving them and the success of the educational process. The research aims to identify the impact of the mobile correspondent strategy in improving some basic football skills for middle school students. The researcher chose the experimental research method because it is appropriate for designing and controlling the research problem. Experimental groups with 20 students for each group, the research sample represented the students of Anbar Vocational Secondary School for Physical Education and Sports Sciences in the city of Ramadi - the fourth stage, the researcher followed a set of field procedures such as sample homogeneity and equivalence procedure to control the influencing factors, educational units were prepared with the mobile correspondent strategy for a period of (6) at a rate of one educational unit per week applied by the experimental group, and after processing the results, the researcher concluded the superiority of the mobile strategy over the traditional method followed, as it showed that the calculated (T) values ​​​​of (2.92-5.42- 6.17) for basic skills tests and respectively the largest correspond (T) table value, but the most important recommendations were to emphasize the use of modern strategies by physical education teachers based on cooperative learning of football skills, and to provide teachers with courses and provide them with information about the mobile reporter strategy and modern strategies in the field of teaching sports skills. bstract should be self-contained, meaning there are no citations are included. It should concisely inform the reader of the manuscript’s purpose, methods, findings, and significance. The abstract should be written in relatively nontechnical language, yet clear enough for an informed reader to understand the manuscript’s contribution. The abstract contains approximately 100-200 words.